2020
DOI: 10.1002/jcph.1758
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Edoxaban Plasma Concentration and Blood Coagulation in Healthy Volunteers Using Standard Laboratory Tests and Viscoelastic Analysis

Abstract: The capability of viscoelastic measurement parameters to screen anticoagulation activity of edoxaban in relation to its plasma concentrations was evaluated in 15 healthy male volunteers. Blood samples were drawn before the oral administration of edoxaban 60 mg and 2, 4, 6, 8, and 24 hours after administration. At each time, standard coagulation tests were performed, blood viscoelastic properties were measured with a thromboelastometry device ROTEM delta analyzer (Instrumentation Laboratory, Werfen, Barcelona, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Several studies pointed out that thromboelastometric tests were applicable to qualitatively monitor the anticoagulant effect of DOACs [ 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 ] ( Table S3 in Supplementary Materials ) and the reversibility of their activity [ 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 ].…”
Section: Oral Anticoagulation: Antivitamin K Antagonists (Vkas) and D...mentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies pointed out that thromboelastometric tests were applicable to qualitatively monitor the anticoagulant effect of DOACs [ 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 ] ( Table S3 in Supplementary Materials ) and the reversibility of their activity [ 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 ].…”
Section: Oral Anticoagulation: Antivitamin K Antagonists (Vkas) and D...mentioning
confidence: 99%
“…Data regarding the use of ROTEM for the evaluation of patients anticoagulated with edoxaban are very limited. Two studies considered the impact of whole blood spikes with edoxaban on the ROTEM assay [ 151 , 164 ]. Seyve et al [ 151 ] reported INTEM-CT to be less sensitive than EXTEM-CT; moreover, EXTEM-CT was above the normal range when the plasma concentrations of edoxaban were about 100 ng/mL.…”
Section: Oral Anticoagulation: Antivitamin K Antagonists (Vkas) and D...mentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies ( 25 , 29 , 38 , 45 , 46 , 55 ) were identified analyzing the effects if edoxaban on viscoelastic testing ( Supplementary Tables 2.1–2.3 ). The CT and R in relation to the edoxaban plasma concentration are shown in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…By the time literature review was concluded there were only two studies assessing the effects of edoxaban on ROTEM showing significant prolongations of EXTEM clotting time (CT) even in therapeutic doses ( 45 , 55 ) ( Table 2.1 ).…”
Section: Resultsmentioning
confidence: 99%